High intensity interval cycling improves physical fitness in trained adults - Petersen, B. A.; Hastings, B.; Gottschall, J. S. (Journal of Fitness Research, 2016)
Introduction: High intensity interval training (HIIT) is a specific type of vigorous intensity exercise characterised by periods of work over 85% maximum heart rate (HRmax). Numerous past studies have documented significant cardiovascular, metabolic, musculoskeletal, and body composition improvements with this type of training, traditionally with cycling Wingate tests. However, popular HIIT sessions outside of research typically incorporate weight-bearing impact, which limits large segments of the population from participating. Thus, a low-impact alternative in a practical format with parallel benefits is an imperative option that requires testing.